Relationship of TikTok For Your Page content on academic procrastination among students - Kristin E. J. Nomleni; Kornelia Erista Setiyanti (Inovasi Kurikulum, 2026)
The increasing use of TikTok has not only made it a medium for entertainment but also has the potential to influence students' academic behavior. This study aims to determine the relationship between exposure to For Your Page (FYP) content on the TikTok application and active academic procrastination among students in the Greater Jakarta area. The S-O-R theory serves as a basis for identifying media stimuli that elicit procrastination responses. The instrument used to measure active academic procrastination is the Active Procrastination Scale, which has been adapted into Indonesian and is valid and reliable. The research method used is a quantitative approach with correlation analysis to test the relationship between the two variables. Data collection was conducted online through questionnaires distributed to students in the Greater Jakarta area. The analysis indicates that active academic procrastination among students is strongly associated with exposure to TikTok FYP content. However, exposure to TikTok FYP content is not the only factor influencing active academic procrastination. Other factors also influence it. In this regard, effective management of social media use is necessary, and it is recommended that other variables that may influence students' academic behavior be examined.   Abstrak Fenomena meningkatnya penggunaan TikTok tidak hanya menjadikannya sebagai media hiburan, tetapi juga berpotensi memengaruhi perilaku akademik mahasiswa. Penelitian ini bertujuan untuk mengetahui hubungan terpaan konten For Your Page (FYP) pada aplikasi TikTok terhadap prokrastinasi akademik aktif pada mahasiswa di wilayah Jabodetabek. Teori S-O-R digunakan sebagai landasan untuk mengetahui stimulus media yang dapat memunculkan respons berupa perilaku prokrastinasi. Instrumen yang digunakan untuk mengukur prokrastinasi akademik aktif yaitu skala active procrastination yang telah diadaptasi ke Bahasa Indonesia dan terbukti valid serta reliabel. Metode penelitian yang digunakan adalah pendekatan kuantitatif dengan analisis korelasi untuk menguji hubungan kedua variabel. Pengumpulan data dilakukan secara daring melalui penyebaran kuesioner kepada mahasiswa di daerah Jabodetabek. Hasil analisis menunjukkan bahwa prokrastinasi akademik aktif pada mahasiswa memiliki hubungan yang kuat dengan terpaan konten FYP TikTok. Meskipun begitu, terpaan media FYP TikTok bukan satu-satunya faktor yang memengaruhi perilaku prokrastinasi akademik aktif karena hal ini juga dapat dipengaruhi oleh faktor lain. Berkaitan dengan hal tersebut, diperlukan pengelolaan penggunaan media sosial secara bijak serta direkomendasikan untuk dapat mengkaji variabel lain yang berpotensi memengaruhi perilaku akademik mahasiswa. Kata Kunci: mahasiswa; prokrastinasi akademik; terpaan FYP; TikTok